Morphological and proteomic analysis of biofilms from the Antarctic archaeon, Halorubrum lacusprofundi - Liao, Y; Williams, TJ; Ye, J; Charlesworth, J; Burns, BP; Poljak, A; Raftery, MJ; Cavicchioli, R (2016)
© The Author(s) 2016. Biofilms enhance rates of gene exchange, access to specific nutrients, and cell survivability. Haloarchaea in Deep Lake, Antarctica, are characterized by high rates of intergenera gene exchange, metabolic specialization that promotes niche adaptation, and are exposed to high levels of UV-irradiation in summer. Halorubrum lacusprofundi from Deep Lake has previously been reported to form biofilms. Here we defined growth conditions that promoted the formation of biofilms and used microscopy and enzymatic digestion of extracellular material to characterize biofilm structures. Extracellular DNA was found to be critical to biofilms, with cell surface proteins and quorum sensing also implicated in biofilm formation. Quantitative proteomics was used to define pathways and cellular processes involved in forming biofilms; these included enhanced purine synthesis and specific cell surface proteins involved in DNA metabolism; post-translational modification of cell surface proteins; specific pathways of carbon metabolism involving acetyl-CoA; and specific responses to oxidative stress. The study provides a new level of understanding about the molecular mechanisms involved in biofilm formation of this important member of the Deep Lake community.